(untitled) (Web of Teachers: Inderscience Research, 2026)
The report explores how precedent phenomena operate within the news style. The author discusses key concepts such as media communication and precedent phenomena, emphasizing their significance. It is argued that employing precedent elements in news serves to enhance expressiveness, engage the recipient’s cognitive processes, and introduce an element of intellectual play, requiring the recipient to interpret the intended meaning. Additionally, the report highlights that precedent phenomena influence how real-world events are perceived—not simply reflected, but reinterpreted by the audience. These phenomena rely on intertextuality as their cognitive basis. Their rich informational content and associative potential enable the efficient and expressive delivery of complex messages.